The prevalence of gestational diabetes in advanced economies - Schneider, Sven; Bock, Christina; Wetzel, Marion; Loerbroks, Adrian (Journal of perinatal medicine, 2012)
One of the first steps in optimizing future prevention and appropriately allocating resources to future diagnosis and treatment of Gestational diabetes (GDM) is to quantify its burden. The aim of this study was therefore to conduct a systematic review of current international literature on the prevalence of GDM with a focus on advanced economies. Based on literature searches with the database “PubMed” we included studies with a publication date between 2000 and 2011. All studies were classified independently by two authors. In accordance with the PRISMA Statement we identified 27 original studies. The prevalence of GDM varies substantially between populations with a range of 1.7-11.6 %. Patient self-reports yield higher prevalence estimates than values that are based on medical diagnosis or clinical diagnostic tests. Prevalence seems to vary considerably within Europe with higher prevalence values being observed in Southern Europe than in Northern and Central Europe. Prevalence values from studies from Australia and North America were within this range. This review provides a comprehensive and sound summary of the current state of research on the prevalence of GDM in advances economies as a fi rst step in identifying starting points for future interventions.